Study of the foot morphology of recreational marathon runners - Chen, L.-H.; Liu, K.-H.; Liu, P.-L.; Wang, M.-J.; Kobayashi, Y.; Chang, C.-C. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2022)
The aim of this study was to explore the characteristics of the foot morphology of recreational marathon runners. We compared the foot dimensions data of recreational marathon runners with the data of non-habitual exercisers. The results indicated that the recreational marathon runners had significantly shorter feet and shorter fibulare instep. The lengths of the toes and halluces on their right feet were significantly shorter than those of the non-habitual exercisers. Based on the analysis of relative foot length, the recreational marathon runners had wider foot breadth, heel breadth, and ball girth circumference. In addition, the arches of recreational marathon runners had a higher arch height index value for both feet.